Chapter 10 Weltbürger Perspectives and Samhandling - Steiro, Trygve J. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The chapter starts with a criticism of management and control concepts that have been rooted in economic or psychological theories and models, although society's complexity and the pace of change will demand a broader and deeper foundation for the development of effective management systems in the future. Other voices need to be put forward. Immanuel Kant (1795/1991) argued for his idea of the Weltbürger ("world citizen"), also known as "The Cosmopolitan Ideal". His fundamental philosophy is that all humans are welcome, regardless of time and place, and that all humans are world citizens, regardless of nationality and cultural belonging (Kant, 1795/1991). All people are co-citizens, independent of nationality and cultural affiliation, and the Weltbürger is concerned with global problems and solutions. Another central thinker is Jacques Derrida (1930-2004), a French philosopher and writer particularly known for the term "Deconstruction", which is about splitting up words and phrases to find out what they really mean, in the light of the culture and underlying attitudes. Human comprehension requires common words and phrases (language), and a cultural and social context, both of which have formed the basis for conceptual analysis of the terms "hospitality" and "threshold of tolerance". The conclusion is that the concepts of the Weltbürger and "hospitality" have important values in and of themselves, and are ideas that are universal and timeless, providing an important compass for samhandling."